Analysis of Gas-Steam CHP Plants Without and with Heat Accumulator and HTGR Reactor - Ryszard Bartnik; Anna Hnydiuk-Stefan; Zbigniew Buryn (Energies)
This study analyzes the thermodynamic and economic viability of modified high-temperature gas-cooled reactor (HTGR) gas-steam combined heat and power (CHP) systems compared to conventional CHP plants. The research addresses the critical need for efficient and sustainable energy production methods. Using comprehensive thermodynamic modeling and economic analysis, the study evaluates system performance under various operating conditions. Key findings reveal that modified CHP plants with HTGR and turboexpanders (TEs) demonstrate significantly higher efficiency and lower heat generation costs compared to conventional gas turbine (GT) CHP plants, despite higher initial capital investments. The modified systems achieve electricity generation efficiencies up to 48%, surpassing traditional nuclear power plants. The absence of CO2 emissions and lower fuel costs in HTGR systems contribute to their economic advantage. This research provides novel insights into the potential of HTGR technology in CHP applications, offering a promising solution for future energy systems. The study’s originality lies in its comprehensive comparison of conventional and modified CHP systems, considering both thermodynamic and economic aspects, which has not been extensively explored in existing literature.